Prevalence, molecular characterisation and phylogenetic analyses of hydatid cysts and cysticercus tenuicollis isolates and first report of E. canadensis (G6/G7) in wild boars in Bingol province, Türkiye - Kilinc, Seyma Gunyakti; Celik, Figen; Kesik, Harun Kaya; Simsek, Sami (Elsevier, 2024)
Wild boars can directly or indirectly transmit numerous zoonotic helminths to humans in rural communities as they serve as reservoir hosts. This study was conducted to determine the occurrence and molecular characterisation of cystic metacestode forms of helminth parasites in wild boar and to identify haplotypes. To this end, 23 wild boar carcasses shot by hunters during the 2023 hunting season were necropsied and all internal organs were examined. Cysticercus tenuicollis (n = 07) and hydatid cyst (n = 10) isolates were obtained from the examined boars. Species identification of Cysticercus and hydatid cyst isolates was performed by amplification of partial fragments of the cox1 gene. According to BLAST search, all sequences of C. tenuicollis isolates were identified as Taenia hydatigena. Out of the hydatid cyst isolates, seven were classified as Echinococcus granulosus sensu stricto (G1/G3) and one sample was identified as Echinococcus canadensis (G6/G7). All isolates of E. granulosus s.s. (G1/ G3) were re-amplified with the NADH dehydrogenase subunit 5 (nad5) in order to distinguish between G1 and G3 genotypes. Based on the sequence analysis, it was found that five of the E. granulosus s.s. isolates were classified as G1, while two were classified as G3. Based on the results of this study, it can be concluded that the G1 genotype is the most prevalent genetic variant among wild boar populations in Bingol province, T & uuml;rkiye. In this study, a total of five novel haplotypes were identified. A previously unidentified haplotype was revealed through the haplotype analysis of E. canadensis (G6/G7). All isolates in the haplotype network of T. hydatigena were shown to exhibit distinct and geographically specific haplotypes. According to the findings of the study, wild boars include a substantial amount of genetic variety in E. granulosus s.s. And T. hydatigena.
Keywords: Wild boar; Hydatid cyst; Cysticercus; Haplotype; T & uuml;rkiye